THEORETICAL AND PRACTICAL BASIS OF IMPLEMENTATION OF DIGITAL TECHNOLOGIES IN IMPROVING THE EFFICIENCY OF INVESTMENT PROJECT MANAGEMENT IN CHEMICAL INDUSTRY ENTERPRISES (Marketing Journal, 2025)
The use of digital technologies in managing investment projects at chemical industry enterprises was examined. The effectiveness of projects was analyzed through the integration of Artificial Intelligence, IoT, Digital Twin, and Big Data. These technologie s were mapped to different stages of the project life cycle, and a conceptual management model was proposed. Based on the analysis, it was demonstrated that the comprehensive adoption of digital tools can improve production quality and resource efficiency. Practical recommendations were developed to enhance implementation in industrial project management.
Keywords: investment project; chemical industry; digital technologies; management; artificial intelligence; IoT; Digital Twin; Big Data 229